A Critical Reflexive Account From Participatory Theater With Asylum Seekers: Lessons for Framing Trauma and Resilience in Refugee Status Determination - Misra, Smita (Frontiers in Communication, 2020)
Critical Health Communication scholars can play a significant role in the asylum seeking process by expanding the legal understanding of migrant trauma. Legal processes like Refugee Status Determination (RSD) define the course of an asylum seeker’s life. Legal determinations hinge on the persuasiveness of narratives of persecution to decide on the legitimacy of asylum claims. Participatory methods, such as participatory theatre, either support or resist legal processes by drawing on narratives of trauma or community engagement, respectively. Methods that rely on trauma narratives validate notions of individual suffering, while methods that use community engagement address the social and communal dimensions of health, including isolation. This essay develops a critical, reflexive account of my situated practices as a theatre practitioner working with asylum seekers, and later, as a character reference for my participants’ legal claim. I show how participatory projects focusing exclusively on promoting migrant resilience through participation can fail to engage with the power that RSD has to determine the course of migrant lives. Importantly, the legal framework of RSD frames an asylum seeker’s every move through the lens of persecution and trauma. As my critical reflections demonstrate, participatory practitioners working with asylum seekers must be aware of how the goals of their engagement may interact with the limitations of the legal process. Such awareness demands strategic forms of engagement aimed at shaping the legal understanding of migrant trauma and persecution.